Knowledge, attitudes, and practices regarding heart failure among Chinese patients: a cross-sectional study - Ping Jin; Zhisong Shu; Kun Cui; Zhenhong Ou; Hongping Li; Yuhui Luo (BMC Public Health)
Abstract Background Understanding patients’ knowledge, attitudes, and practices is essential for effective heart failure (HF) management, as these factors significantly influence self-care behaviors, treatment adherence, and clinical outcomes. This study aimed to investigate the knowledge, attitudes, and practices (KAP) of patients with heart failure. Methods A web-based cross-sectional study was conducted from April to May 2023 among 483 heart failure patients recruited through convenience sampling. Inclusion criteria encompassed a confirmed HF diagnosis and the ability to independently use mobile devices. The research employed a self-administered questionnaire, validated through expert review and pilot testing, to assess knowledge, attitudes, and practices. The overall reliability was robust (Cronbach’s α = 0.875), with subscale alphas of 0.819 for knowledge, 0.582 for attitudes, and 0.846 for practices. Results The findings from 483 HF patients revealed limited knowledge (mean score: 10.75 out of 20), moderately negative attitudes (mean score: 22.93 out of 40), and relatively proactive practices (mean score: 32.21 out of 45). Higher knowledge levels and having mid-range ejection fraction emerged as significant predictors of proactive health behaviors (all P < 0.05). Structural equation modeling further demonstrated that education and marital status positively influenced knowledge, while attitudes unexpectedly showed a negative association with practices (all P < 0.05). Conclusion This study highlights critical gaps in knowledge and attitudes among HF patients, despite some proactive practices. By leveraging a web-based platform, this research contributes to the growing literature on digital health approaches in chronic disease management, suggesting that scalable, technology-enabled education and support strategies should be integrated into HF care. Additionally, this study provides novel insights into the unexpected negative relationship between attitudes and practices, underscoring the complexity of behavioral change in HF management. Clinical trial number Not applicable.